Aging Methods—An Evaluation of Their Influence on Bond Strength - Teixeira, Gabriela Simões; Pereira, Gabriel Kalil Rocha; Susin, Alexandre Henrique (European Journal of Dentistry, 2021)
Objectives To evaluate the effect of different artificial aging methods on the bond strength of a resin composite associated with a universal adhesive (Scotchbond Universal) used under two etching approaches (self-etch [SE] or etch-and-rinse [ER]) to enamel and dentin substrates.Materials and Methods A total of 96 noncarious human third molars were prepared and randomly divided according to three factors (n = 6): substrate (enamel and dentin), adhesive approach (SE and ER), and aging method (water storage for 24 hours, 6 months, or 1 year; subjected to 10,000, 20,000, or 30,000 thermal cycles; and sodium hypochlorite [NaOCl] storage for 1 or 5 hours).Statistical Analysis Microshear bond strength tests were conducted, and the collected data (MPa) were subjected to three-way analysis of variance (ANOVA) with post hoc Bonferroni tests (p < 0.05) and Weibull analysis. The failure pattern was also evaluated.Results Three-way ANOVA revealed that the factors “substrate” (p = 0.00) and “aging method” (p = 0.00) had a significant effect on the bond strength, but the factor “adhesive approach” did not (p = 0.84). The bond strength in the enamel group for the SE approach was negatively affected under 20,000 and 30,000 thermal cycles. Weibull presented the highest m in the NaOCl storage for the 5 hours group to enamel using the SE and to dentin using ER approaches. Adhesive/mixed failures were predominant for all groups.Conclusion Thermocycling aging (20,000 and 30,000 cycles) significantly reduced the bond strength to enamel using the SE approach. On the contrary, storage with the NaOCl method proved to increase bond strength under the evaluated conditions.
Keywords: artificial aging; interface degradation; hydrolysis; universal adhesive